2017
DOI: 10.2141/jpsa.0160110
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Methionine or Arginine Levels on the Urinary Creatinine Excretion in Broiler Chicks

Abstract: Two experiments were conducted to evaluate the usefulness of urinary creatinine levels as a criterion for the estimation of protein and amino acid requirements in poultry. Here we studied the effects of dietary precursor levels of creatinine, methionine and arginine, on urinary creatinine excretion in experiments. Both experiments used 15 Chunky broilers chicks that were 8 days old. The chicks were assigned to three dietary groups, with five chicks each, and were fed an experimental diet for 7 days. The experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
0
4
1
Order By: Relevance
“…Therefore, the most important dietary amino acids are the essential amino acids arginine and methionine. Hasegawa et al found that UCrn excretion increased in a dose-dependent manner based on dietary levels of arginine and methionine (43). Although we compared the composition of amino acids in the LP, in which UCrn was elevated, to the amino-acid compositions in the SP and HP, we did not find larger quantities of arginine or methionine.…”
Section: Discussioncontrasting
confidence: 59%
“…Therefore, the most important dietary amino acids are the essential amino acids arginine and methionine. Hasegawa et al found that UCrn excretion increased in a dose-dependent manner based on dietary levels of arginine and methionine (43). Although we compared the composition of amino acids in the LP, in which UCrn was elevated, to the amino-acid compositions in the SP and HP, we did not find larger quantities of arginine or methionine.…”
Section: Discussioncontrasting
confidence: 59%
“…In our study, plasma creatinine levels increased with increasing Met levels from deficient (Low-Met) to 30% higher (High-Met). Hasegawa et al (2017) declared that Met or arginine might become a limiting amino acid for creatine synthesis when Met or arginine was deficient in the diet. Other creatine precursors might become limiting amino acids for creatine biosynthesis when Met or arginine was excess in diet.…”
Section: Plasma Metabolitesmentioning
confidence: 99%
“…For the analysis, MT concentration was represented as a ratio of MT to creatinine in order to control for the quantity of water in the urine samples, which enables the comparison of MT levels between individuals [ 4 , 18 , 24 , 29 ]. The creatinine concentration of each urine sample was measured using a commercially available kit, which was previously used for droppings of other avian species [ 5 , 8 ], based on the Jaffe reaction method (Item No. 500701, Cayman Chemicals).…”
mentioning
confidence: 99%